From Transparency and Governance to Compliance: How Tax Digitalization Shapes Business Sustainability - Triwibowo, Edi; Purba, Jamian (Journal of Applied Accounting and Taxation, 2025)
This study investigates the effects of tax transparency and corporate governance on tax compliance, with tax digitalization as a moderating variable, among companies operating in the Cikarang–Cibitung industrial area. Grounded in legitimacy theory, the research posits that transparent tax practices, strong governance structures, and digital integration enhance organizational legitimacy and compliance. A quantitative research design was employed using survey data from 300 respondents involved in tax-related functions across manufacturing, trade, and service sectors. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that tax transparency significantly and positively affects tax compliance (β = 0.187, p < 0.001), supporting the notion that openness fosters trust and mitigates noncompliance risks. Similarly, corporate governance positively affects compliance (β = 0.169, p < 0.01), underscoring the importance of accountability and ethical oversight. The moderating analysis shows that tax digitalization strengthens the effects of both transparency (β = 0.221, p < 0.05) and governance (β = 0.198, p < 0.05) on compliance, indicating that digital platforms enhance efficiency and monitoring in tax administration. The model explains 65% of the variance in tax compliance (R² = 0.65), demonstrating robust explanatory power. These findings affirm legitimacy theory’s proposition that organizations maintain societal trust by adopting transparent, responsible, and digitally adaptive tax practices. The study contributes theoretically by integrating digital transformation into legitimacy-based frameworks and offers practical implications for policymakers and corporate leaders aiming to strengthen sustainable tax compliance.